2022
DOI: 10.1155/2022/4324635
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Significance of HALP Index for Colon Cancer Patients in a Hispanic-Based Population

Abstract: Background. Survival and recurrence rates following locoregional colon cancer surgical resection are highly variable. Currently used tools to assess patient risk are still imperfect. In the present work, we evaluate, for the first time, the prognostic value of the recently developed HALP (hemoglobin, albumin, lymphocyte, and platelet) index in Hispanic colon cancer patients. Patients and Methods. We conducted a retrospective cohort study in Mexican patients with a nonmetastatic colon cancer diagnosis who under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The current research explores the association between HALP score and colorectal cancer, primarily focusing on overall survival and disease-free survival outcomes [10,24,25]. Research studies have demonstrated that when the HALP score above a specific threshold, there is a correlation with improved survival outcomes [24][25][26]. In our study, we endeavored to examine the correlation between the HALP score and perioperative morbidity in the context of right colon surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The current research explores the association between HALP score and colorectal cancer, primarily focusing on overall survival and disease-free survival outcomes [10,24,25]. Research studies have demonstrated that when the HALP score above a specific threshold, there is a correlation with improved survival outcomes [24][25][26]. In our study, we endeavored to examine the correlation between the HALP score and perioperative morbidity in the context of right colon surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic inflammation stimulates angiogenesis, immunosuppression and supports the formation of microenvironment, thus promoting the initiation, progression and metastasis of tumor cells ( Calderillo Ruiz et al, 2022 ). Recently, research has focused on the impact of nutritious status on a cancer patient’s prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…HALP score has been used by many researchers to predict the prognosis in several types of cancers for the last few years. [6][7][8] Hb and albumin can reflect the nutritional status of the patient and albumin alone has been considered as a positive prognostic factor for cancer patients. Lymphocyte and platelet values can give a hint of the patients' immune status; already included in scores like platelet-to-lymphocyte ratio.…”
Section: Introductionmentioning
confidence: 99%